New and Bioactive Natural Products Isolated from Madagascar Plants and Marine Organisms - Hou, Y.; Harinantenaina, L. (Current Medicinal Chemistry, 2010)
Madagascar, the world's fourth biggest island has a unique biodiversity. The interest on the phytochemical investigation of Malagasy plant and marine natural products started from the isolation of the potent anti-cancerous bisindole alkaloids: vinblastine and vincristine. In this paper, work published in the last two decades (1991-2009) on 262 new natural products isolated from Malagasy higher plants, liverworts and marine organisms is reviewed. Several results on the bioassays of the isolated new natural products have been reported.
Keywords: natural products